Nasal Foreign Bodies in Children: A Literature Review - Wasiniewska, Weronika; Barański, Marcin; Kandefer, Tomasz; Sroka, Maria Izabela; Kosek, Szymon; Klonowska, Justyna; Walkowski, Radosław Jan (Quality in Sport, 2025)
Nasal foreign bodies (NFBs) are a common pediatric emergency, particularly in children aged 2–4 years, driven by exploratory behavior and inadequate supervision. These objects, ranging from beads to button batteries, can cause symptoms such as nasal discharge, obstruction, and epistaxis. Complications include chronic sinusitis, rhinolith formation, and tissue necrosis, with button batteries posing significant risks due to chemical burns. Diagnosis relies on clinical examination and imaging when necessary. Management involves techniques like positive pressure or endoscopic removal, with general anesthesia for complex cases. This review aimed to collect, systematize, and summarize the available knowledge on NFBs in children by utilizing systematic reviews, meta-analyses, and clinical studies. Preventive strategies emphasize caregiver education, safe storage practices, and product redesign to reduce risks and improve outcomes.